2008
DOI: 10.1080/02678370802564272
|View full text |Cite
|
Sign up to set email alerts
|

The mediating role of work-to-family conflict in the relationship between shiftwork and depression

Abstract: With significant segments of the working population involved in shiftwork, there is the possibility of serious health outcomes. There are two possible pathways to ill health. In the biological pathway the body's circadian rhythms are affected, leading to physiological disturbances and the inability to cope. By contrast, the aim of this study is to elucidate a social pathway by which shiftwork may lead to mental ill health. It examines the mediating influence of work-to-family conflict in the association betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
34
1
10

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 76 publications
4
34
1
10
Order By: Relevance
“…Fewer mental health problems are expected when living with a partner [4,47,80], in households with young children [42,47,79], and those that have low-strain relationships with spouse or children [8,23,47], higher household incomes [41,84], less work-family conflicts [12, 33,75], and greater access to the support of social network outside the workplace [22,47,73].…”
Section: The Multilevel Determinants Of Workers' Mental Healthmentioning
confidence: 99%
“…Fewer mental health problems are expected when living with a partner [4,47,80], in households with young children [42,47,79], and those that have low-strain relationships with spouse or children [8,23,47], higher household incomes [41,84], less work-family conflicts [12, 33,75], and greater access to the support of social network outside the workplace [22,47,73].…”
Section: The Multilevel Determinants Of Workers' Mental Healthmentioning
confidence: 99%
“…Furthermore, there is evidence to suggest that shift work may impair mental wellbeing and increases the risk for psychological distress (Vogel et al 2012, Baron and Reid 2014). It has been suggested that some of the effects of shift work on mental health may be mediated by social difficulties in terms of imbalance between work and private life (Haines et al 2008). Shift work has also been inferred as a risk factor for sick leave; currently, however, this seems primarily to apply to female healthcare workers on fixed evening work (Merkus et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…These include impacts on health and psychosocial well-being, such as work-family conflict,2 increased fatigue,3 problems with adapting and readapting to night work,4 and an increased risk for cardiovascular disease,5 gastrointestinal problems,6 7 and cancer 8…”
Section: Introductionmentioning
confidence: 99%